The house on Olive Street - Carr, Robyn (Don Mills, Ont. : MIRA, 1999)
After the death of their close friend, four women spend a summer sorting through personal effects and discover themselves, and a dream, along the way.
Keywords: Middle aged women -- Fiction; Bereavement -- Fiction; Female friendship -- Fiction; Self-realization -- Fiction; California -- Fiction; Domestic fiction